Prevalence and Nematode Infection Level on Gastrointestinal Tract at Horse (Equus caballus) in Bangkalan Madura - Elok Apriliawati; Mufasirin Mufasirin; Wurlina Wurlina; Poedji Hastutiek; Lucia Tri Suwanti; Benjamin Christoffel Tehupuring (Journal of Parasite Science (JoPS), 2019)
The purpose of this study is to determine the prevalence, infection level, sex and age effect on the infection level of GIT Nematode parasite in a horse. The fecal samples analyzed using the methods of native, sedimentation, floatation, and worm eggs count per gram of feces. Sample examination found 54 positive infected gastrointestinal nematode parasite with prevalence rate of 87% (54 from 62). The prevalence of Trichonema sp., Strongylus sp., and Parascaris equorum are 37.1%, 16.1%, and 1.6%. There were also mixed infestation like Strongylus sp. and Trichonema sp; Strongylus sp. and Parascaris equorum; Trichonema sp. and Parascaris equorum with total prevalence 27.4%, 1.6%, and 3.2%. Sex and age of horse had a very significant and significant effect in prevalence and infection level of Nematode parasite.